The effect of rituals on the socialization of employees An applied study of a sample of Maisan governorate staff - Mahdi Hussein Jabrb - Abdul Hussein Jassim Muhammad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Our current study aimed to know the main role of rituals as an independent variable in its impact on organizational socialization and to clarify the relationship of correlation and influence between the variables of the study in the light of the previous contributions of each variable by a group of researchers and to test this relationship. Show the similarity of the nature of the relationship between the variables of the study. The practical side of the study was applied in the office of Maysan Governorate, which is the local authority in the governorate and to which many state institutions are linked. Of the sample members are employees whose appointment did not pass one year, and the total number of form s valid for transfer was 209 forms, after the researcher distributed 230 forms and 219 forms were retrieved, 5 forms were lost and 6 forms were not completely filled out. The total response rate was 90.8%, in order to test the main hypotheses of the study. Main and subsidiary The researcher used a set of statistical tools, namely: the normal distribution test .Confirmative factor analysis, Cronbach stability coefficient (alpha), standard deviation, DSP coefficient of variation ,relative importance. Pearson Correlation Coefficient and Structural Equation Modeling) The researcher relied on a set of ready-made programs for statistical analysis, namely (SPSS23), (Amos 23) and (Microsoft Excel 2010). The study reached a set of conclusions, the most prominent of which was the existence of a correlation and effect of positive statistical significance between rituals and organizational socialization. In the wake of the conclusions ,the researcher made a set of recommendations, the most important of which was the call for the administration in the office of the governorate of Maysan to allow work on ritual behaviors and financial flexibility in management and listening .To employees' opinions, aspirations and suggestions.